Evaluation of working conditions of workers engaged in tending horses - Bożena Nowakowicz-Dębek; Halina Pawlak; Łukasz Wlazło; Izabela Kuna-Broniowska; Hanna Bis-Wencel; Agnieszka Buczaj; Piotr Maksym (Annals of Agricultural and Environmental Medicine, 2014)
[b]introduction[/b]. A growing interest in the horse business has resulted in the increased engagement of many people in this area, and the health problems occurring among workers create the need to search for prophylactic measures. [b]objective[/b]. The objective of the study was evaluation of the level of exposure to air pollution in a stable, and estimation of the degree of work load among workers engaged in tending horses. [b]material and methods[/b]. The study was conducted twice, during the winter season, in a stable maintaining race horses, and in a social room. In order to evaluate workers’ exposure, air samples were collected by the aspiration method. After the incubation of material, the total number of bacteria and fungi in the air was determined, as well as the number of aerobic mesophilic and thermophilic bacteria, expressed as the number of colony forming units per cubic meter of air (CFU/m[sup]3[/sup]). The measurement of total dust concentration in the air was also performed, simultaneously with the measurement of microclimatic parameters. The study of work load also covered the measurement of energy expenditure, evaluation of static physical load, and monotony of movements performed. [b]conclusions[/b]. The stable may be considered as a workplace with considerable risk of the occurrence of unfavourable health effects.